Fungsi Bahasa pada Wacana Berasan Etnik Rejang di Kabupaten Lebong - Mahmud Yunus; Dian Eka Chandra Wardhana; Sarwit Sarwono (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2020)
The purpose of this study was to describe the function of language in the procession of Berasan in the Rejang ethnic group in Lebong Regency. The research method uses qualitative content analysis methods. The main data of this research is in the form of oral text on Berasan. Data collection techniques using documentation, observation, and interviews. Data analysis techniques are by means of interpreting the content of communication, both in text and in context, reading symbols, and interpreting the content of symbolic interactions that occur in communication. Test the validity of the data using triangulation of data sources and member check. The results showed that the custom of Rejang ethnic Berasan in Bioa Sengok Village, Rimbo Pengadang District, Lebong Regency was dominated by 67.74% referential functions while directive and fatigue functions were complementary functions respectively 25.80% and 6.43%. The function that is very influential on the Berasan event is the directive function so that there is an agreement between the two prospective brides in carrying out the marriage. Although in fact, this Berasan event is a traditional formality event because the agreement has been discussed by both parties, especially the prospective groom and the bride before the Berasan event is held.